Association Between Serum TLR-4 Levels and Severity Scores in Adult Sepsis Patients - Peter Leonardo; Novita Anggraeni; Vera Muharrami (Faculty of Medicine-Universitas Airlangga, 2026)
Introduction: Toll-like receptor-4 (TLR-4) is a proximal innate-immune sensor implicated in sepsis pathophysiology. Whether circulating TLR-4 levels track organ dysfunction and bedside severity scores remain clinically relevant. Objective: To examine the correlation between serum TLR-4 and (i) acute physiology and chronic health evaluation (APACHE) II and (ii) sequential organ failure assessment (SOFA) scores among adults with sepsis admitted to a provincial referral intensive care unit (ICU). Methods: We conducted an analytic cross-sectional study at Arifin Achmad General Hospital, Riau, Indonesia (February to September 2025). Adults (≥18 years) with Sepsis-3 were enrolled consecutively. Exclusions included cardiogenic shock, end-stage kidney disease, and pregnancy. Serum TLR-4 was measured in duplicate using enzyme linked immunosorbent assay (ELISA) (450 nm). APACHE II (worst values in first 24 h) and baseline SOFA were recorded the same day. Normality was tested with Shapiro–Wilk; Spearman’s rho assessed associations (two-tailed, α=0.05). Result and Discussion: Thirty-nine patients were included. Median (range) of TLR-4 was 1.8 (0.18–7.03) ng/mL, Median (range) of SOFA total was 9 (4–17) and APACHE II total was 21 (10–44). TLR-4 correlated positively with APACHE II total (r=0.470, p=0.003) and SOFA total (r=0.458, p=0.003). TLR-4 also correlated with SOFA coagulation (r=0.380, p=0.017), liver (r=0.438, p=0.005), and renal (r≈0.43, p<0.01) subscores. These findings demonstrate moderate positive correlations, suggesting that TLR-4 may complement established severity assessment tools in monitoring physiologic derangement and multi-organ dysfunction in sepsis. The findings should be interpreted considering the relatively small sample size and single-center cross-sectional design. Conclusion: Serum TLR-4 associates with APACHE II and SOFA at presentation and may complement early risk stratification in adult sepsis.